An Overview of Epidemiology of COVID-19 in Macau S.A.R - Sin Man Ieng; Io Hong Cheong (Frontiers Media S.A., 2020)
The Greater Bay Area of southern China has a population of over 71 million people. The area is well-connected with Hubei province, the epicenter of the COVID-19 outbreak. Macau, as the most densely populated city in the world, is very vulnerable to infectious disease outbreaks. Since its return to the sovereignty of China 20 years ago, the city has experienced outbreaks such as severe acute respiratory syndrome (SARS), Swine flu, and COVID-19. At the time of writing, 10 confirmed imported/local transmission cases were recorded. The government undertook measures to attain and then maintain 40 days without new cases. In this article, we report on the 10 confirmed cases and discuss the measures that the Macau Special Administrative Region (S.A.R.) government undertook during the COVID-19 pandemic.